2020
DOI: 10.1371/journal.pone.0232811
|View full text |Cite
|
Sign up to set email alerts
|

Potential short-term negative versus positive effects of olive mill-derived biochar on nutrient availability in a calcareous loamy sand soil

Abstract: In the present work, the olive mill solid waste (OMSW)-derived biochar (BC) was produced at various pyrolytic temperatures (300-700˚C) and characterized to investigate its potential negative versus positive application effects on pH, electrical conductivity (EC), and nutrients (P, K, Na, Ca, Mg, Fe, Mn, Zn, and Cu) availability in a calcareous loamy sand soil. Therefore, a greenhouse pot experiment with maize (Zea mays L.) was conducted using treatments consisting of a control (CK), inorganic fertilizer of NPK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The pH of RL, DL, and LSRNF was determined in a mixture (1:25, w/v) in deionized water using a digital pH meter. The samples were extracted to measure the EC using a digital EC meter . The VM, A, and FC of RL and DL were measured following the standard procedure, developed by the American Society for Testing and Materials (ASTM) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of RL, DL, and LSRNF was determined in a mixture (1:25, w/v) in deionized water using a digital pH meter. The samples were extracted to measure the EC using a digital EC meter . The VM, A, and FC of RL and DL were measured following the standard procedure, developed by the American Society for Testing and Materials (ASTM) .…”
Section: Methodsmentioning
confidence: 99%
“…The samples were extracted to measure the EC using a digital EC meter. 34 The VM, A, and FC of RL and DL were measured following the standard procedure, developed by the American Society for Testing and Materials (ASTM). 35 The structural stability was identified by XRD.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors (Senesi andPlaza, 2007;Dias et al, 2010) stated that acidic compounds produced from decomposition of soil organic matter lowered the pH of alkaline soils. For calcareous soils also, biochar additions increased the soil pH (Alazzaz et al, 2020). However, application of acidic biochars produced through slow pyrolysis and steam activation reduced the soil pH between 0.2 and 0.4 units in calcareous soils (Ippolito et al, 2016).…”
Section: Soil Phmentioning
confidence: 99%
“…Biochar itself contain significant quantities of cations like K, Ca, Mg and application of that improved their levels in the soil (Jien and Wang, 2013). Alazzaz et al (2020) reported that biochar derived from the olive mill solid waste should be restricted in calcareous loamy sand soils as it reduced the concentration of P, Ca, Mg and Mn in maize shoots. In calcareous loamy sand soils, biochar application increased the available K, Na, Ca, Mg, AB-DTPA extractable Fe and Mn whereas it reduced AB-DTPA extractable Zn.…”
Section: Potassiummentioning
confidence: 99%
“…These results are in agreement with previous reports of Joseph and Taylor (2014), Yargicglu et al(2015), PT 350 was found to have the most in uence on soil pH (which decreased) compared to PT 500 and PT 700 . These results could be attributed to the increase in basic oxides and carbonates produced during the pyrolytic process(Alazzaz et al 2020). These results are in line with previous studies(Cardelli et al 2017;Yao et al 2017 andTang et al 2019), which reported that soil pH increased with increasing pyrolysis temperature.…”
mentioning
confidence: 99%